Marriage Legal Aspects On The Status Of Out Of Marriage Children In Birth Certificates And Child Protection - Daud Munasto; Oci Senjaya (IHSA Institute, 2022)
Children are buds, potentials, and the younger generation as the successor to the ideals of the nation's struggle that has a strategic role. Children have special characteristics and characteristics that ensure the continuity of the existence of the nation and state in the future. Children are the living messages we send to a time we will not see (children are the living messages we send for a time we don't see), that's how John W Whitehead in Lenny N. Rosalin describes the importance of children as the next generation as well as the greatest asset for the future. front. Every newly born child must be registered immediately in the form of a Birth Certificate as the child's identity even though the child's status is out of wedlock without losing the rights of the child. This study uses a normative juridical method that is descriptive in nature, which is a systematic and comprehensive description of the object under study. The legal materials used are secondary data consisting of primary, secondary and tertiary legal materials. This research is a library research (library research). To obtain the data presented in this study, the authors used the legal materials obtained were analyzed qualitatively normatively and explained deductively. So that in the end get the expected results, to then draw a conclusion as the final result of this research. The conclusion of this thesis is that the Constitutional Court Decision No. 46/PUU-VIII/2010 which states that Article 43 paragraph (1) of Law Number 1 of 1974 concerning Marriage, namely: